Early Childhood Motor Development and Parent Socio-economic Status - Stephani, Mesa Rahmi; Sumarno, Gano; Wibowo, Ricky (Universitas Pendidikan Indonesia, 2019)
This study was aimed at determining the relationship between early childhood motor development and the level of socio-economic status (SES) of parents. The research method used was Ex-post Facto comparative study. The population of the study involved children aged 4-5 year from early childhood education schools in urban areas. 50 samples were selected (male = 27; female = 23). Overall sample participation was 78%. So that the representative sample were 39 participants. Children motor development was measured by using the Ages and Stages Questionnaire (ASQ) 3rd Edition. To measure the Socio-Economic Status (SES), an Instrument for Measuring the Socioeconomic Status of a family was used. The results showed that the early childhood motor development was not only influenced by parents' socioeconomic status, it was also influenced by playgrounds available in schools and the playing space at home. This study shows that parents today understand the importance of early childhood education in optimizing children development. Schools and neighborhoods are two best investments for a better children' future. Â Â AbstrakStudi ini bertujuan untuk mengetahui keterkaitan perkembangan motorik anak usia dini dengan tingkat status sosial ekonomi (SES) orang tua. Metodologi penelitian menggunakan studi komparasi Ex-post Facto. Populasi penelitian melibatkan anak usia 4-5 tahun berasal dari sekolah pendidikan anak usia dini yang berada di daerah perkotaan. Sampel dipilih sebanyak 50 (laki-laki = 27; perempuan = 23). Partisipasi sampel keseluruhan sebesar 78%. Sehingga sampel yang representatif sebanyak 39. Perkembangan Motorik anak diukur menggunakan Ages and Stages Questionaire (ASQ) 3rd Edition. Sedangkan untuk mengukur Status Sosial Ekonomi (SES) menggunakan Instrument (Scale) for Measuring the Socioeconomic Status of a family. Hasil penelitian menunjukkan bahwa perkembangan motorik anak usia dini tidak hanya dipengaruhi faktor status sosial ekonomi orang tua, juga dipengaruhi oleh tempat bermain yang tersedia di sekolah dan lingkungan bermain di rumah. Penelitian ini menunjukkan bahwa orang tua saat ini semakin memahami pentingnya pendidikan anak sejak dini dalam mengoptimalkan perkembangan anak. Sekolah dan lingkungan tempat tinggal merupakan salah satu wujud investasi terbaik untuk masa depan anak yang lebih baik.